The Expression Modulation of the Key Enzyme Acc for Highly Efficient 3-Hydroxypropionic Acid Production - Wang, Sumeng; Jin, Xin; Jiang, Wei; Wang, Qian; Qi, Qingsheng; Liang, Quanfeng (Frontiers in Microbiology, 2022)
3-Hydroxypropionic acid (3-HP) is a promising high value-added chemical. Acetyl-CoA carboxylase (Acc) is a vital rate-limiting step in 3-HP biosynthesis through the malonyl-CoA pathway. However, Acc toxicity in cells during growth blocks its ability to catalyze acetyl-CoA to malonyl-CoA. The balancing of Acc and malonyl-CoA reductase (MCR) expression is another an unexplored but key process in 3-HP production. To solve these problems, in the present study, we developed a method to mitigate Acc toxicity cell growth through Acc subunits (AccBC and DtsR1) expression adjustment. The results revealed that cell growth and 3-HP production can be accelerated through the adjustment of DtsR1 and AccBC expression. Subsequently, the balancing Acc and MCR expression was also employed for 3-HP production, the engineered strain achieved the highest titer of 6.8 g/L, with a high yield of 0.566 g/g glucose and productivity of 0.13 g/L/h, in shake-flask fermentation through the malonyl-CoA pathway. Likewise, the engineered strain also had the highest productivity (1.03 g/L/h) as well as a high yield (0.246 g/g glucose) and titer (up to 38.13 g/L) in fed-batch fermentation, constituting the most efficient strain for 3-HP production through the malonyl-CoA pathway using a cheap carbon source. This strategy might facilitate the production of other malonyl-CoA-derived chemical compounds in the future.